Rozwiązane

Pomoże ktoś?
( 5x+2)×2 =
-3 (4×+2)=
3 (2×-5)=
-5 ( -4×+1)=
Z góry dziękuję za pomoc



Odpowiedź :

Odpowiedź:

( 5x+2)×2 =10x+4

-3 (4×+2)= -12x-6

3 (2×-5)= 6x -15

-5 ( -4×+1)= 20x -5

pozdro:)

Szczegółowe wyjaśnienie:

Korzystamy z rozdzielności mnożenia względem dodawania/odejmowania:

[tex]a\cdot(b\pm c)=a\cdot b\pm a\cdot c[/tex]

[tex](5x+2)\cdot2=5x\cdot2+2\cdot2=10x+4\\\\-3(4x+2)=-3\cdot4x+(-3)\cdot2=-12x-6\\\\3(2x-5)=3\cdot2x+3\cdot(-5)=6x-15\\\\-5(-4x+1)=-5\cdot(-4x)+(-5)\cdot1=20x-5[/tex]